A new genus and two new species of the tribe Meconematini (Orthoptera: Tettigoniidae) from China - Shi, Fu-Ming; Bian, Xun; Chang, Yan-Lin (Zootaxa, 2013)
The study deals with one new genus and two new species, i. e. Allicyrtaspis gen. nov., Allicyrtaspis globosis sp. nov. and Allicyrtaspis conicicersus sp. nov. from China, and provides generic and species descriptions and diagnoses.